Sustainability of productive use of off-grid renewable energy: A case of a women’s collective from rural India - Ingole, Chandrakant Kashiram (International Journal of Management and Sustainability, 2023)
Renewable energy has emerged as a climate-friendly development alternative to provide clean and reliable energy access. However, the long-term sustainability of off-grid-based applications for productive and income-generating activities remains in suspect as it is an emerging area of development and has yet to be extensively studied for sustainability. With this background, this paper proposes a new framework for the assessment of the sustainability of productive use of off-grid energy based on technical, economic, social, institutional, and environmental dimensions. To ensure it is deeply rooted in practice, a survey-based study of a women-collective from rural India was conducted using the proposed framework. The results indicated that capacity development, participatory approaches, need assessment, and regular cash flows were a few of the important indicators for sustainability of operations. Further, it was also observed that sustainability and socio-economic benefits were intertwined and complementary. The Indian Government envisions a substantial role for renewable energy-enabled productive use to address infrastructure bottlenecks, development issues, and climate change related goals. In this context, the proposed framework would be useful for assessing the sustainability of such interventions for their longevity while accruing socio-economic benefits to the users.